A Spatio-Temporal Analysis of Gender Related Educational Development Index of Uttar Pradesh - Pal, Pooja; Singh, Suman (National Geographical Journal of India, 2022)
Literacy is an important indicator of human resource development. It is crucial for the overall development of society as it has the potential to increase human capital, removes inequality from society, affects the growth of employment opportunities, and above all liberates them from social evil. As in the development process, both men and women play an equally crucial role but the fruits of development are not equally shared among them. Therefore the study of literacy and its differential on the gender of an area is indispensable. According to Census (2011), literacy rate of India is 74.04% out of which the male literacy rate is 82.14% and female literacy rate is 65.46% and has a huge gender gap of 16.60% while at the state level in Uttar Pradesh this gender gap figure amounts to 20.10%. From a population point of view Uttar Pradesh is a very important state of the country as 16.17% of India’s population lives in the state and as literacy is one of the important measures of any region’s human resource development. This paper is an attempt to evaluate the Gender disparity present in the literacy level of Uttar Pradesh. For this GenderRelated Educational Development Index (GEDI) has been used on the lines of Human Development Index of UNDPto measure the disparity level. The paper uses the data of two consecutive census i.e. 2001- 2011 to measure the GEDI both in a spatial and temporal context. It is found that the state has improved as the GEDI value increased from 0.530 in 2001 to 0.662 in 2011, showing that there still exists a disparity which needs to be reduced.